2006
DOI: 10.14310/horm.2002.11166
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sex steroids and circulating homocysteine in healthy Greek postmenopausal women

Abstract: Endogenous estrogens and not androgens are related to serum homocysteine values in postmenopausal women. Whether this association has clinical implications remains to be clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…Also, the ovarian steroid (estradiol) showed significant positive association with homocysteine among test group (r=0.367, p ≤ 0.05), while the control group showed a weak negative association (r= -0.225, p ≤ 0.05). Equally, findings from this study corroborate earlier reports by Christodoulakos et al (2006) in which the plasma HCY levels dropped with increasing estrogen level. However, Osunkalu et al (2015) shows that the ovarian steroids did not show significant association with serum HCY levels in both infertile and fertile women.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the ovarian steroid (estradiol) showed significant positive association with homocysteine among test group (r=0.367, p ≤ 0.05), while the control group showed a weak negative association (r= -0.225, p ≤ 0.05). Equally, findings from this study corroborate earlier reports by Christodoulakos et al (2006) in which the plasma HCY levels dropped with increasing estrogen level. However, Osunkalu et al (2015) shows that the ovarian steroids did not show significant association with serum HCY levels in both infertile and fertile women.…”
Section: Discussionsupporting
confidence: 92%
“…Proposed mechanisms relate to an increase in methionine synthase activity, transamination of methionine, or interfering with transsulfuration pathway resulting in irreversible catabolism of homocysteine to cysteine. 24 While the exact mechanism awaits further research, we have demonstrated in the current study that estradiol replacement counteracts the effect of dietary-induced increase in homocysteine level, a finding that is consistent with the following published animal and clinical observations: (1) estradiol-treated rats had lower total homocysteine concentrations ( P < .001) than those in nonestradiol-treated groups 12 ; (2) oral estrogen lowers plasma homocysteine levels in postmenopausal women, with the greatest effect in women in the higher quartile of plasma homocysteine levels at baseline 22,23,25,26 ; and (3) higher estrogen status is associated with a decreased mean serum total homocysteine concentration, independent of nutritional status and muscle mass, and that estrogen may explain the previously reported male–female difference in total homocysteine concentration. 27…”
Section: Discussionsupporting
confidence: 88%
“…However, we observed a statistically significant association between MTHFR Ala222Val polymorphism and androgenicity, BMI, and WHR. Insulin resistance bears an independent positive association with total testosterone and FAI (30), while it correlates positively with indices of obesity such as BMI and WHR (31). We propose the following hypothesis: genetic defects in Hcy metabolism may result in impaired Hcy catabolism which, at a cellular level, may lead to endothelial dysfunction thus causing insulin resistance.…”
Section: Discussionmentioning
confidence: 92%